Pengaruh Literasi Keuangan dan Inklusi Keuangan terhadap Keputusan Investasi Mahasiswa Universitas Muhammadiyah Palopo - Hildawati Nurdin; Asriany; Jumawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to analyze the impact of financial literacy and financial inclusion on investment behavior. The study uses a quantitative method approach, with a population of 160 and a sample of 62 respondents taken from the Slovin formula. Data was collected through questionnaires and analysis using validity tests, reliability tests, multiple linear regression analysis results, T tests, F tests, R2 tests. Shows that investment, but financial inclusion has a significant influence on investment decisions, and financial education and financial inclusion simultaneously have a significant influence on investment decisions.